Survey on Improvement and Application of Grover Algorithm - LIU Xiao-nan, SONG Hui-chao, WANG Hong, JIANG Duo, AN Jia-le (Jisuanji kexue, 2021)
Quantum information science is a new interdisciplinary subject,which has unique performance in the field of information.It can break through the limits of the existing classical information systems in the aspects of improving computing speed,ensuring information security,increasing information capacity and improving detection accuracy.Grover algorithm is a typical quantum algorithm,which can realize quadratic acceleration for any classical brute force exhaustive search problem,further promoting the development of quantum computing.How to effectively improve and apply Grover algorithm has become an important research field of quantum computing.This paper summarizes the optimization,improvement and application of Grover algorithm,summarizes the application and improvement of Grover algorithm in different fields,and discusses some research directions of future algorithm improvement and related applications of Grover algorithm.